Encapsulation of Plant Extract Compounds Using Cyclodextrin Inclusion Complexes, Liposomes, Electrospinning and Their Combinations for Food Purposes - Lopez-Polo, J; Muñoz-Shuguli, C; Patiño-Vidal, C (Elsevier Ltd, 2021)
Background: Plant extract compounds have various industrial applications as well as some limitations. However, the encapsulation of them through different techniques is known as a way for optimizing their physicochemical properties, biological activities, and effectivity to improve the shelf-life of different foods. Scope and approach: In this review, the latest food applications of cyclodextrin inclusion complexes, liposomes, and electrospinning as encapsulating methods of plant extract compounds were compared. Moreover, all possible combinations of these methods and their application in food research were deeply discussed. Key findings and conclusions: Cyclodextrin inclusion complexes have been used to encapsulate hydrophobic compounds, while liposomes and electrospinning allow encapsulating of both, hydrophilic and/or hydrophobic compounds. Furthermore, cyclodextrin itself is a kind of “ready encapsulating (wall) material” that allows the formation of inclusion complexes, while in liposomes and electrospinning the formation of wall material is required. Most reported applications with cyclodextrin inclusion complexes and electrospinning focus mainly on the development of food packaging materials. In contrast, liposomes have been widely used to produce edible films and food coatings. Moreover, the use of cyclodextrin inclusion complexes and liposomes as ingredients has allowed to obtain functional foods with better physicochemical and sensory properties. On the other hand, the double or triple combination of these methods have also been reported, and the key benefits of them have been the improvement of encapsulation parameters and encapsulated compound properties, as well as the prolongation of the shelf-life of foods where the encapsulated compound (through combining methods) was applied. © 2020 Elsevier Ltd